Preliminary investigation on coconut oil-based self-emulsifying formulation for the delivery of Metronidazole - Yahaya, Zwanden Sule; Yahaya, Paul Osereme; Mohammed, Boma Blessing (Nigerian Journal of Pharmaceutical and Applied Science Research, 2020)
The aim of this study was to perform a preliminary evaluation of the suitability of natural coconut oil in the formulation of a self-emulsifying drug delivery system (SEDDS) for metronidazole. Different SEDDS mixtures comprising of different proportions of coconut oil, cremophor EL (surfactant) and PEG-400 (co-surfactant) of varying mass ratios were prepared. A pseudo-ternary phase diagram was generated from the phase titration studies between water and the different SEDDS mixtures at room temperature which facilitated the selection of a stable SEDDS. The stable SEDDS was then loaded with the metronidazole powder and characterized with respect to globule size, polydispersity index (PDI), emulsification time, stability, post-dilution drug precipitation and in vitro release studies. It was also converted to powder by adsorption on cabosil® at 1:2 (w/w) ratio and evaluated. The formulation consisted of 20 % coconut oil, 60 % cremophor EL, 20 % PEG-400 and demonstrated stability against phase separation. Also, it exhibited an emulsification time of 15.0 s, a mean globule size of 18.95 nm, a polydispersity index (PDI) of 0.238 and released over 90 % of the drug within 30 min. The powdered formulation demonstrated acceptable flow properties, contains particles that are irregular and free from rough edges. At 20 min, the percentage of drug released from the metronidazole-SEDDS powder during the in vitro release studies was 37 % lower than the liquid metronidazole-SEDDS, indicating that solidification of lipid-based formulations through adsorption onto a carrier may limit drug release. The experimental results from this preliminary investigation were satisfactory, indicating that natural coconut oil can serve as a promising alternative colloidal drug carrier in the field of novel drug delivery systems.